2009
DOI: 10.1097/aln.0b013e3181aae897
|View full text |Cite
|
Sign up to set email alerts
|

Clonidine as an Adjuvant to Local Anesthetics for Peripheral Nerve and Plexus Blocks

Abstract: The effect of adding clonidine to local anesthetics for nerve or plexus blocks remains unclear. The authors searched for randomized placebo-controlled trials testing the impact of adding clonidine to local anesthetics for peripheral single-injection nerve or plexus blocks in adults undergoing any surgery (except eye) without general anesthesia. Twenty trials (1,054 patients, 573 received clonidine) published 1992-2006 tested plexus (14 brachial, 1 cervical) and nerve blocks (2 sciatic/femoral, 1 midhumeral, 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
232
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 344 publications
(252 citation statements)
references
References 33 publications
13
232
0
7
Order By: Relevance
“…Whereas the effectiveness in the analgesic duration may be similar for perineural adjuvants regardless of type of local anesthetic, the relative increase in the duration of analgesia is far more pronounced with intermediate-acting local anesthetics than with long-acting local anesthetics. 2 Although magnesium is likely to prolong the analgesic duration without reference to any local anesthetics, the clinical relevance of adding magnesium to a long-acting local anesthetic may be questioned because the relative gain will be minimal. Furthermore, mixed epinephrine to bupivacaine could have masked any pharmacodynamic effect of perineural magnesium, similar to the report in which clonidine failed to prolong the analgesic duration of ropivacaine and bupivacaine with epinephrine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas the effectiveness in the analgesic duration may be similar for perineural adjuvants regardless of type of local anesthetic, the relative increase in the duration of analgesia is far more pronounced with intermediate-acting local anesthetics than with long-acting local anesthetics. 2 Although magnesium is likely to prolong the analgesic duration without reference to any local anesthetics, the clinical relevance of adding magnesium to a long-acting local anesthetic may be questioned because the relative gain will be minimal. Furthermore, mixed epinephrine to bupivacaine could have masked any pharmacodynamic effect of perineural magnesium, similar to the report in which clonidine failed to prolong the analgesic duration of ropivacaine and bupivacaine with epinephrine.…”
Section: Discussionmentioning
confidence: 99%
“…However, the increased risk of hypotension, fainting, and sedation may limit its usefulness. 2 The addition of dexamethasone to bupivacaine and clonidine has been shown to prolong the analgesic duration of brachial plexus blocks. This effect may be secondary to a local action of dexamethasone on nociceptive C-fibre mediated via glucocorticoid receptors and anti-inflammatory action.…”
Section: Résumémentioning
confidence: 99%
“…Respecto a los coadyuvantes se ha visto que los agonistas de los receptores alfa-2 adrenérgicos 20,21 (clonidina y dexmetomidina) prolongan de forma significativa la analgesia postoperatoria (122 minutos) de bloqueos realizados sobre el miembro superior, pero producen importantes efectos adversos como sedación e hipotensión. Estudios realizados en cirugía de PTR donde se han utilizado los agonistas alfa-2 (clonidina y efedrina) como coadyuvantes, no han demostrado mayor eficacia o analgesia del bloqueo femoral, por tanto no están recomendados actualmente para su uso como coadyuvantes a los AL en el bloqueo femoral en PTR (recomendación A, evidencia 1) 110 .…”
Section: Coadyuvantes a Los Anestésicos Locales Para Prolongar El Blounclassified
“…Se han realizado diversos estudios que tenían como objetivo prolongar la duración de los bloqueos locorregionales añadiendo a los AL coadyuvantes [18][19][20] como adrenalina, opioides, ketamina o midazolam, obteniéndose una efectividad limitada. Los agonistas de los receptores alfa-2 adrenérgicos (clonidina 20 y dexmetomidina 21 ) sí han demostrado prolongar de forma significativa la analgesia pero con importantes efectos adversos.…”
unclassified
“…Dexmedetomidine is a α2 -adrenoceptor agonist, which induces sedative state similar to physiological sleep [78,79]. Several studies have shown that propofol impairs neutrophil, monocyte and macrophage functions.…”
Section: Intravenous Anestheticsmentioning
confidence: 99%